2011
DOI: 10.1128/cvi.05373-11
|View full text |Cite
|
Sign up to set email alerts
|

Altered Eosinophil Proteome in a Patient with Hypereosinophilia from Acute Fascioliasis

Abstract: We used comparative proteomics to analyze eosinophils from a patient with hypereosinophilia due to fascioliasis. Using 2-dimensional electrophoresis and mass spectrometry, we demonstrated that the eosinophil proteome was significantly altered compared to those of healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In dengue virus, P4HB was linked to a reduction of β1 and β3 integrins allowing for the entry of the virus (68) and in MA104 cells, thiol blockers, and P4HB inhibitors decreased the entry of rotavirus (66). The other recurring human protein is GANAB, which is related to the alteration of eosinophil proteome (69). Strikingly, eosinophils are important mediators of allergies, asthma, and adverse drug reactions, and are also related to the host defense mechanisms against helminth infections, which are characterized by eosinophilia (7072).…”
Section: Discussionmentioning
confidence: 99%
“…In dengue virus, P4HB was linked to a reduction of β1 and β3 integrins allowing for the entry of the virus (68) and in MA104 cells, thiol blockers, and P4HB inhibitors decreased the entry of rotavirus (66). The other recurring human protein is GANAB, which is related to the alteration of eosinophil proteome (69). Strikingly, eosinophils are important mediators of allergies, asthma, and adverse drug reactions, and are also related to the host defense mechanisms against helminth infections, which are characterized by eosinophilia (7072).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are capable of modulating kainate receptors and their effect depend greatly upon the receptor composition [120,121]. Both proteins increase current amplitude, and glutamate affinity for all homomeric receptors, and significantly reduce inward rectification, but their modulation on desensitization kinetics is different [86,120,121]. kinetics.…”
Section: The Kainate Receptor Auxiliary Subunitsmentioning
confidence: 98%
“…However, a study carried out in NETO1 Knockout mice demonstrated that NMDA mediated currents were not affected by this mutation [86]. On the other hand, Amyloid Precursor Protein (APP) infusion increases NMDAR evoked currents [87] and together with its related proteins, amyloid precursor-like proteins 1 and 2 (APLP1 & APLP2), enhance surface NMDA receptors expression in vitro [88].…”
Section: The Nmda Receptor Auxiliary Subunitsmentioning
confidence: 98%
“…Prior proteomic studies have described alterations in amounts of eosinophil proteins in subjects with atopic dermatitis and eosinophilia ( 46 ), mildly elevated eosinophil counts associated with seasonal birch pollen allergy ( 47 ), and eosinophilia associated with Fasciola hepatica infection ( 48 ). In these studies, eosinophil proteins from affected individuals or healthy controls were separated by two-dimensional electrophoresis to produce high-resolution maps of protein-stained spots.…”
Section: Prospects For the Futurementioning
confidence: 99%